2019
DOI: 10.1098/rsif.2019.0547
|View full text |Cite
|
Sign up to set email alerts
|

Helical fibrillar microstructure of tendon using serial block-face scanning electron microscopy and a mechanical model for interfibrillar load transfer

Abstract: Tendon's hierarchical structure allows for load transfer between its fibrillar elements at multiple length scales. Tendon microstructure is particularly important, because it includes the cells and their surrounding collagen fibrils, where mechanical interactions can have potentially important physiological and pathological contributions. However, the three-dimensional (3D) microstructure and the mechanisms of load transfer in that length scale are not known. It has been postulated that interfibrillar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…2017; Magnusson & Kjaer, 2019; Safa et al . 2019). Patellar tendons in rats and Achilles and patellar tendons in mice demonstrated the highest level of Col1a1 expression, but there was divergence between species for Col1a2 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2017; Magnusson & Kjaer, 2019; Safa et al . 2019). Patellar tendons in rats and Achilles and patellar tendons in mice demonstrated the highest level of Col1a1 expression, but there was divergence between species for Col1a2 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ECM of tendons is composed of numerous proteins that work in conjunction to transmit forces between muscles and bones. Type I collagen, which is a fibrillar molecule composed of distinct α-1 and α-2 chains, is the major protein constituent of tendons and bears much of the mechanical loads placed on tendons (Sarver et al 2017;Magnusson & Kjaer, 2019;Safa et al 2019). Patellar tendons in rats and Achilles and patellar tendons in mice demonstrated the highest level of Col1a1 expression, but there was divergence between species for Col1a2 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated fibril tortuosity is given in Fig. 2 F. These results display greater tortuosity than Safa et al found [67] . They reported that τ is typically less than 1%, whereas, here, we found the distribution of τ to be centred around 5%.…”
Section: Observed Microstructural Measurementsmentioning
confidence: 52%
“…2.6.3. Fibril chirality calculations Fibrils have been observed to follow helical paths within tendon [67] . To quantify the helical nature of fibrils, in this work, the fibril paths in the x − y plane were used, collapsing the z-direction.…”
Section: Fibril Alignment Calculationsmentioning
confidence: 99%
“…changes throughout tendon development, demonstrating greater structural order ( i.e ., fewer bifurcations and less interweaving) in mature compared to fetal tendons ( Provenzano and Vanderby, 2006 ). Further, some of these interweaving collagen fibrils may be retained in mature tendon and their contributions to mechanical function are being evaluated, with evidence that friction between helical fibrils transfers mechanical loads ( Safa et al ., 2019 ; Szczesny et al ., 2017 ). Overall, further work is needed in mammalian systems to identify specifically how LOX and LOXL1-4 are regulated during tendon development, as well as better differentiate between changes to collagen crosslinking and the broader changes to ECM structure.…”
Section: Lox Production and Activationmentioning
confidence: 99%